Comparative Optimization of Cellulase and Laccase Enzymes in Deinking Process of Used Newspapers - Saharman Gea; Noni Oktari; Andriayani Andriayani; Sri Rahayu; Averroes F Piliang (Jurnal Kimia Sains dan Aplikasi, 2020)
The use of enzymes in the bio-deinking process of newspaper waste has promising potential. However, investigations on the concentration of enzyme combinations need to be carried out to obtain the optimum ratio of cellulase and laccase enzymes for the bio-deinking process of recycled newspapers. The mixture of the two enzymes at various ratios was used to remove the ink on paper pulp from used newspapers by mechanical disintegration method treatment and followed by the bio-deinking process in an incubator shaker. The characterization of functional groups, structures, and thermal properties of bio-deinked pulp paper was carried out by FTIR, XRD, DTG/TGA, and an analysis of the degree of brightness to the prepared paper. FTIR results confirmed three main components of papers, such as cellulose, hemicellulose, and lignin. The XRD results showed that the equal ratio of cellulase and laccase enzymes had an effect on a higher crystallinity index, which was 78.8% compared to those obtained from the conventional methods with a crystallinity index of 69.7%. Thermal analysis showed that the optimum combination of both enzymes contributed the most at the highest temperature where the rate of degradation decreased. Brightness analysis showed that bio-deinking had met the quality requirements for newsprint paper in SNI 7273:2008. Our findings show that the combination of cellulase and laccase enzymes at the same ratio can produce optimal bio-deinked pulp for paper fabrication with excellent characteristics in brightness, thermal, and physical properties.